Influence of age on manifestation, VC and TLCO values, and bronchoalveolar lavage cell counts of sarcoidosis and extrinsic allergic alveolitis. (10th February 2014) - Sterclova, Martina; Paluch, Peter; Skibova, Jelena; Vasakova, Martina
Abstract Introduction Immune response probably changes during human life, being influenced by cumulative exposure to environmental factors and individual genetic background. Methods Patients investigated for suspected interstitial lung disease were prospectively enrolled. After completing the diagnostic process, 121 patients were diagnosed extrinsic allergic alveolitis (EAA) and 136 sarcoidosis. Three groups according to age were established (<30 years, 30–60 years, >60 years), clinical manifestation, vital capacity (VC), forced expired volume in 1 s (FEV1), lung diffusing capacity for carbon monoxide‐transfer factor (TLCO) and bronchoalveolar lavage fluid (BALF) differential cell count were compared among the groups. Results Age subgroups of EAA patients did not significantly differ in lung functions. In the group above 60 years, non‐significantly higher neutrophils and eosinophils counts and CD4/CD8 ratio were observed. Sarcoidosis patients were significantly younger than EAA group and had significantly better lung functions (VC, FEV1, TLCO). Patients with sarcoidosis above 60 years of age had significantly higher percentages of neutrophils in BALF compared with younger patients. BALF percentage of neutrophils positively correlated with age. Conclusions Presented results may support the hypothesis that reactivity of immune system changes during the life, which may result in different manifestation of interstitial lung diseases according to age.